Increased erythrocyte aggregation and oxidative stress in patients with idiopathic interstitial pneumonia - Ugurlu, Erhan; Kilic-Toprak, Emine; Altinisik, Goksel; Kilic-Erkek, Ozgen; Cengiz, Betul; Kucukatay, Vural; Senol, Hande; Akbudak, Ismail Hakki; Ekbic, Yusuf; Bor-Kucukatay, Melek (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Hemorheological properties are important determinants of tissue oxygenation. Although hemorheological alterations in various lung diseases have been well-defined, no information is available about the effects of idiopathic interstitial pneumonia (IIP) on hemorheological parameters. Objectives: The aim of this study was to investigate hemorheological parameters (erythrocyte deformability, aggregation, and plasma viscosity -PV) and associated oxidative stress indices in patients with IIP. Methods: The study enrolled 31 patients (9 Idiopathic pulmonary fibrosis (IPF), 10 non-specific Interstitial Pneumonia (NSIP), 12 Cryptogenic Organising Pneumonia (COP) and 33 healthy controls. Erythrocyte deformability and aggregation were measured by an ektacytometer. PV was determined by a cone-plate rotational viscometer and oxidative stress via a commercial kit. Results: Erythrocyte aggregation, total oxidant status (TOS) and oxidative stress index (OSI) of IIP patients were higher than controls whereas erythrocyte deformability, PV and total antioxidant status (TAS) were unaltered. Conclusions: Increment of oxidative stress in IIP seems to depend on enhancement of oxidants, rather than alteration of antioxidants. The issue that, elevated erythrocyte aggregation may further impair tissue oxygenation by disturbing microcirculation in IIP, may be considered in the follow up and development of new treatment protocols for this disease.